1984
DOI: 10.1111/j.1469-8137.1984.tb06104.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Trenching and Coring on the Formation of Ectomycorrhizas on Birch Seedlings Grown Around Mature Trees

Abstract: SUMMARYInitially non-mycorrhizal seedlings of birch {Betula pendula Roth.) were grown for a season around two 11-year-old birch trees on an experimental site south of Edinburgh. Some seedlings (non-isolated) were planted in undisturbed positions, others (trenched) in volumes of soil isolated from the mature tree by trenches, and yet others (cored) in cores of soil (8x10 cm diameter) that had been removed and replaced immediately.Mycorrhizas of Lactarius pubescens (Fr. ex Krombh.) Fr., Lactarius glyciosmus (Fr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 14 publications
1
47
0
Order By: Relevance
“…These fungi might thus correspond to 'late stage' fungi (Deacon, Donaldson & Last, 1983;Fleming, 1984). P. croceum frequently occurs in old, mature conifer and broad-leaf forests where it forms networks of mycelial strands.…”
Section: Discussionmentioning
confidence: 99%
“…These fungi might thus correspond to 'late stage' fungi (Deacon, Donaldson & Last, 1983;Fleming, 1984). P. croceum frequently occurs in old, mature conifer and broad-leaf forests where it forms networks of mycelial strands.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, several fungi such as Truncoeolumella citrina failed to establish primary colonization on hosts such as fir but did succeed in establishing secondary colonization on fir after presumably first de\ eloping primary colonization with a 'compatible' host (Douglas fir). This variation of colonization potential is reminiscent of a phenomenon documented by Fleming (1984), in which seedlings of Betula pendula Roth. formed ectomycorrhizas with different groups of fungi when planted in trenched versus undisturbed areas.…”
Section: Isolates Of R Subcaerulescens R Truncatus R Vulgaris Tmentioning
confidence: 99%
“…1 ; Table 3). Fleming (1983Fleming ( , 1984 was the first to stress that seedlings around trees are colonized by EM fungi typical of the old trees. Thereafter, several studies using baiting seedlings have confirmed this to be a general pattern (Fleming et al, 1986 ;Dahlberg & Stenstro$ m, 1991 ;Newton, 1991 ;Simard et al, 1997b ;Ka/ re!…”
Section: mentioning
confidence: 99%
“…Smith & Read, 1997). Seedlings around trees are colonized by EM fungi typically found in adult trees (Fleming, 1983(Fleming, , 1984. It has been suggested that the EM fungi colonizing roots in natural communities originate from the mycelial network in forest soil more frequently than from spores (cf.…”
mentioning
confidence: 99%